Mapping intangibilities in creative tourism territories through tangible objects: a methodological approach for developing creative tourism offers - Cabeça, Sónia Moreira; University of Algarve - ESGHT (2019)
How can individuals express their perceptions of local places through valued objects and links to their area? Can objects create narratives about places’ identity and collect significant cultural information that connect people to local spaces? Can cultural mapping thus be a useful tool in the design of creative tourist offers? To address these questions, the CREATOUR project organised a series of idea laboratories with various entities that provide creative tourism experiences. The goal was to approach cultural mapping through objects as a way for regional actors to discover what is ‘so special’ about their places and link tourism offers with the communities in which they take place. These exercises led participants to discuss their region’s importance and idiosyncrasies, providing evidence of cultural mapping’s significant role in producing more sustainable offers and better overall destination marketing. Mapping intangibilities through tangible objects helps capture what gives meaning to particular places.